(Re)negotiating illegal migrant identities in selected Zimbabwean fiction. Issue 3 (2nd September 2018) - Mangena, Tendai
Abstract : Since the late 1990s, migrations from Zimbabwe as a result of the country's collapsed economy, have resulted in a number of shifts in the country's literature. Aspects of literary creativity affected are varied, but the most important shift commented on in this article is the thematic focus on the undocumented migrant protagonists' journeys from their homeland and their experiences in the host countries. The discussion focuses on the representation of the various survival strategies employed by undocumented migrants in circumventing immigration laws as they move to and stay in the host countries. The strategies include border jumping and identity masking. Representations of the said subversions of immigration laws are interrogated as manifested in Harare North, We need new names and The crossing, 'My cousin-sister Rambanai' and 'Everything is nice, Zimbulele '. The analysis is done in the context of Hing's theory of migrant illegality and De Genova's 'spectacles of illegality'.